Optimization of the operation of Drăgan-Iad hydropower development using Flower Pollination Algorithm. Issue 1 (1st September 2022) - Tică, E-I; Neagoe, A; Popa, F; Popa, B
Abstract: For the operation of a large hydropower development, it was imagined as optimization problem to realize an annual planned energy generation with monthly imposed fractions. It was conceived a model based on a flower pollination algorithm. Simulations were done for mean hydrological year, with imposed minimal and maximal volumes, for five initial volumes in the reservoir and in two hypotheses related to the imposed annual energy. For imposing realization of the designed energy, for the initial volume into the reservoir set to three lowest values, the planned energy is not realized because the volume into reservoir reaches the minimum allowable volume at the end of the year. For larger volumes at the beginning of the year, the planned annual energy is realized. For the planned annual energy imposed at a lower value, for the three lowest volumes into the reservoir at the beginning of the year the planned energy is realized, and for the other two larger values the program realizes a larger energy generation because, during the year, the volume into the reservoir reach the maximum allowable volume and it was compulsory to operate the hydropower plant to lower the volume. The overall conclusion of the paper is that FPA is very efficient for solving this type of optimization problem applied to a large hydropower development.